(untitled) (Revista Contexto & Educação, 2024)
The improvement of emotional intelligence is essential for individual well-being, social life, academic performance, and work. Therefore, it is necessary to develop strategies within formal education to improve emotional balance and learning, especially after the COVID-19 pandemic. In this context, a scope review was carried out to raise publications about Emotional Intelligence in the formal school environment, and identify gaps and challenges. The review was carried out in databases, according to the "scoping review" methodology. Information was collected from the Virtual Health Library (VHL), Scopus (Sc) and Web of Science (WoS). The keywords “Education”, “Emotional” and "Intelligence” were used, collecting articles published in the last five years. Initially, 541 articles were obtained, 120 met the inclusion criteria and were analyzed. The review shows that works on Emotional Intelligence (EI) have begun to occupy spaces in formal education, focusing more on secondary and higher levels. No works were identified in Vocational Education Integrated to High School, nor in the early grades of kindergarten. It is, therefore, a gap to be filled, since the development of emotional balance is fundamental to the work and must be developed from the initial grades to obtain better results. The review identified several bottlenecks for the promotion of Emotional Education in formal environments, among them: the need to incorporate it across the school curriculum; need to implement/evaluate long-term actions; need to improve data collection instruments, as well as sample size and profile.